Melville's other lives : bodies on trial in The piazza tales - Sten, Christopher, 1944- (Peculiar bodies : stories and histories, 2022)
"This book analyzes the six stories in Melville's 'The Piazza Tales' with an emphasis on issues of embodiment-invalidism or disability, pain, trauma, enslavement, performance, monsters-and related systems of cultural values defined by race, class, and gender"--